Cultural adaptation and assessment of validity evidence for scores obtained using a French version of the Tolerance of Ambiguity in Medical Students and Doctors scale - Motte, Baptiste; Aiguier, Grégory; Reumaux, Pauline; Forzy, Gérard; Piermatteo, Anthony; Ficheux, Guillaume; Vanpee, Dominique; Cobbaut, Jean-Philippe (Mesure et évaluation en éducation, 2021)
Preparing students to deal with and tolerate uncertainty or ambiguity is a major issue in medical education. There are many English-language scales to assess tolerance of uncertainty and ambiguity but no French-language scale has ever demonstrated validity evidence for its scores. We selected the Tolerance of Ambiguity in Medical Students And Doctors (TAMSAD) scale. Through a structured process, the original questionnaire was translated, culturally adapted, and assessed after being administered to a sampling of medical students. Test-retest reliability was verified by presenting the questionnaire to the students again after two months. The assessment of internal consistency revealed satisfactory value. Test-retest reliability is assessed by intraclass correlation that presents good reproducibility of scores obtained by students in first completion and second completion. These results indicate that the French version of the TAMSAD scale can be used to assess French medical students’ tolerance to ambiguity.